Pinus serotina Michx., Pond Pine - Audrey C. Plauche; Gage D. LaPierre; Michael G. Andreu (EDIS)
This publication provides an in-depth profile of Pinus serotina for the use of interested laypersons with some knowledge of biology as well as the academic audiences.